2018
DOI: 10.1167/iovs.18-24363
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors in University Students in Central China: The Anyang University Students Eye Study

Abstract: Citation: Wei S, Sun Y, Li S, et al. Refractive errors in university students in Central China: the Anyang University Students Eye Study. Invest Ophthalmol Vis Sci. 2018;59:4691-4700. https://doi.org/10.1167/ iovs.18-24363 PURPOSE.To assess the prevalence of refractive errors and associated factors in university students in urban areas of Anyang, Central China.METHODS. This is a cross-sectional university-based study of 16-to 26-year-old students in China. Subjects from two universities were invited to undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 56 publications
1
33
1
Order By: Relevance
“…Myopia is a public health problem [9] with a high prevalence especially in the Far East [10]. Onset and progression of myopia has been associated with genetic and environmental factors [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is a public health problem [9] with a high prevalence especially in the Far East [10]. Onset and progression of myopia has been associated with genetic and environmental factors [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In central China, the prevalence rate of myopia was 3.9% in grade 1 children and 67.3% in grade 7 children [2]. A higher prevalence of 83.2% for myopia and 11.1% for high myopia was found in central Chinese university students [3].…”
Section: Introductionmentioning
confidence: 86%
“…The Anyang University Students Eye Study (AUSES) is a university-based, cross-sectional study in which comprehensive ophthalmologic examinations were performed among university students in Anyang, Henan Province, located in central China. The detailed sample selection and methodology have been described previously [3]. Briefly, participants were selected from both the two public universities in Anyang, using random cluster sampling based on grade level.…”
Section: Participantsmentioning
confidence: 99%
“…Research in Singapore revealed that the prevalence of myopia is 62.0% in children age 7 to 9 years 5 and in Guangzhou, China, the prevalence is 49.7%. 6 Among university students in central China, the myopia prevalence is 83.2%, 7 and it is 96.5% in 19-year-old men in Seoul, Korea. 8 The reported prevalence of myopia is 11.9% in Australia, 9 20.0% in the United States, 10 21.1% in urban India, 11 and 16.5% in Nepal.…”
Section: Introductionmentioning
confidence: 99%